THE EDUCATIONAL CONTENT OF PESULAP MERAH IN EXPOSING SHAMANISTIC PRACTICES IN INDONESIA: A CONTEXTUAL STUDY OF THE HADITH ON AL-KAHANAH - Friyadi, Arif (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2024)
Shamanistic practices, such as love spells and black magic, remain widely believed in Indonesian society, reinforcing the stereotype of shamans as figures who can solve mystical problems. This phenomenon has deep roots, stretching back to the eras of animism and dynamism, and continues today amid a lack of scientific understanding. Recently, Pesulap Merah has taken to digital platforms to openly criticize and expose these practices, prompting many to question the claims about shamans' supernatural powers. This study seeks to explore the relevance of the hadith on al-kahanah, which forbids shamanistic practices, in light of Pesulap Merah's critiques. Using a qualitative approach, we gathered data through content analysis of the hadiths in Kutub al-Sittah, along with observations of societal reactions to Pesulap Merah's content. Our analysis involved a comparative examination of the hadiths and an exploration of the motivations behind these critiques. The findings reveal that shamanistic practices not only conflict with Islamic teachings but also promote irrational thinking. While Pesulap Merah's criticisms are not rooted in religious doctrine, they resonate strongly with the hadith's warnings about the dangers of shamanism and its effects on faith and rationality. This research contributes to a deeper understanding of how religious teachings intersect with contemporary socio-cultural issues in Indonesia. [Praktik perdukunan, seperti pelet dan santet, masih banyak dipercaya oleh masyarakat Indonesia sehingga memperkuat stigma dukun sebagai tokoh yang dianggap mampu mengatasi masalah-masalah mistis. Fenomena ini mengakar sejak era animisme dan dinamisme, dan terus berlanjut hingga era modern dengan minimnya pemahaman saintifik. Baru-baru ini, Pesulap Merah, melalui konten-konten digitalnya, secara terbuka mengkritik dan membongkar praktik perdukunan, membuat banyak pihak mulai meragukan klaim kesaktian para dukun. Penelitian ini bertujuan untuk menjelaskan relevansi hadis al-kahanah, yang mengharamkan praktik perdukunan, dengan kritik yang disampaikan Pesulap Merah terhadap praktik-praktik tersebut. Dengan menggunakan pendekatan kualitatif, data dikumpulkan melalui analisis konten dari hadis-hadis al-kahanah yang terdapat dalam Kutub al-Sittah, serta observasi fenomena yang terjadi di masyarakat terkait konten digital Pesulap Merah. Analisis dilakukan dengan pendekatan perbandingan syarah hadis serta analisis motif tindakan. Hasil penelitian menunjukkan bahwa praktik perdukunan tidak hanya bertentangan dengan ajaran Islam, tetapi juga menjerumuskan masyarakat ke dalam pola pikir yang tidak rasional. Kritik Pesulap Merah, meskipun tidak berbasis agama, memiliki relevansi kuat dengan ajaran hadis terkait bahaya perdukunan dan dampaknya terhadap keimanan dan rasionalitas. Penelitian ini berkontribusi dalam kontekstualisasi ajaran agama dengan fenomena sosial-kultural kontemporer di Indonesia.]